The Habit of Lying: Sacrificial Studies in Literature, Philosophy, and Fashion Theory - Smyth, John Vignaux (Duke University Press, 2002)
Frontmatter -- Contents -- Acknowledgments -- Introduction -- Part One. Philosophy -- 1. The Liar as Scapegoat: Rationality and Unanimity -- 2. The Analytics of Fiction -- Part Two. Literature -- 3. Lying for No Reason: Lying and Obscenity in Defoe -- 4. Lies and Truths: Mimetic- Sacrificial Falsification in Stendhal -- 5. Fundaments and Accidents: Mimesis and Mendacity in Molloy -- 6. The Violence of Fiction: Concealment and Sacrifice in Malone Dies and The Unnamable -- Part Three. Fashion Theory -- 7. Fashion Theory -- Conclusion -- Appendix: On René Girard and Paul de Man -- Notes -- Bibliography -- Index